2010
DOI: 10.3109/13693780903453287
|View full text |Cite
|
Sign up to set email alerts
|

L-DOPA accessibility in culture medium increases melanin expression and virulence ofSporothrix schenckiiyeast cells

Abstract: Melanin is a complex polymer widely distributed in nature and has been described as an important virulence factor in several pathogenic fungi, including Sporothrix schenckii. The aim of the present work was to investigate the presence of melanin on the surface of S. schenckii yeast cells which showed differences in their virulence depending on the culture conditions under which they were grown. Yeast cells were cultivated in brain heart infusion (BHI) broth from Difco and Oxoid. BHI from these two vendors are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…This electrondense material visualized by TEM is morphologically similar to the melanin granules described by Teixeira et al (2010). In addition, flow cytometry analysis using antimelanin antibodies showed that miltefosine-treated cells had increased melanin content compared to untreated cells.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…This electrondense material visualized by TEM is morphologically similar to the melanin granules described by Teixeira et al (2010). In addition, flow cytometry analysis using antimelanin antibodies showed that miltefosine-treated cells had increased melanin content compared to untreated cells.…”
Section: Discussionmentioning
confidence: 52%
“…3b). Teixeira et al (2010) have described similar electron-dense material inside the cell wall as melanin deposits. Treatment with 0.5 mg ml 21 of miltefosine induced changes in the ultrastructure of S. brasiliensis yeast cells, such as: decrease in cytoplasmic electron density (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the limited effect of the therapy imposed on these groups is observed, since the growth of the microorganism was observed. What can be expected is that the isolate used, even if it consists of a wild culture with all its mechanisms of defense and exchange of genetic material, can present a greater sensitivity to the therapy since there are different types of Sporothrix schenckii cataloged, with several genotypes 10,11 . Thus, this study indicated the efficiency of methylene blue as a photosensitizer associated with a low power laser in inhibiting the growth of Sporothrix schenckii complex fungi.…”
Section: In Vitro Reduction Of Pathogenic Sporothrix Schenckii Fungusmentioning
confidence: 99%
“…However, due to the indiscriminate use of these drugs, drug-resistant isolates can be identified, which consequently leads to therapeutic failures and remission of mycosis in humans [6][7][8][9] . The diagnosis consists of the microscopic identification of yeast structures of the Sporothrix schenckii complex fungi by the material collected from the lesions 10,11 . Cutaneous sporotrichosis affects people of any age, both sexes, and in various locations favorable to the fungus.…”
Section: Introductionmentioning
confidence: 99%